Quotient and Homomorphism in Ternary Semihyperrings (Journal of Informatics and Mathematical Sciences, 2024)
Ternary semihyperring is an algebraic structure with one binary hyper operation and ternary multiplication. In this paper, more characterizations and some properties of the ternary semihyperring are presented. Moreover, the quotient ternary semihyperrings are constructed via another relation and the isomorphism theorems are proved.